Y=3x-5
y-3x=-5
Times 2 from both side
y(2)-3x(2)=-5(2)
2y-6x=-10
Times negative from both side
(-)2y-6x(-)=(-)-10
-2y+6x=10
or
6x-2y=10
6x=2y+10
6x-2y=10
Furthermore, we see that both equation have the same 6x-2y=10 which means that both of them have infinity solutions, not a solution. Hope it help!
Answer:
4 - 7g
Step-by-step explanation:
Combine like terms: 5 - 9 - 7g = -4 - 7g (answer)
Answer:
a) x = 1.52
b) s = 1.16
Step-by-step explanation:
We have that:
5 students watched 0 movies.
9 students watched 1 movie.
5 students watched 2 movies.
5 students watched 3 movies.
1 student watched 4 movies.
(a) Find the sample mean x.
Sum divided by the number of students. So
(b) Find the approximate sample standard deviation, s.
Standard deviation of the sample.
Square root of the sum of the squares of the values subtracted from the mean, divided by the sample size subtracted by 1. So
Answer:
5 cups
I would appreciate Brainliest but no worries.